EVALUATION OF THE EFFECTIVENESS OF AN EDUCATIONAL INTERVENTION ON IMPROVING KNOWLEDGE OF MOTOR REHABILITATION AMONG PRIMARY CAREGIVERS OF STROKE PATIENTS AFTER HOSPITAL DISCHARGE AT THE CENTER FOR REHABILITATION IN BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of an educational intervention in improving knowledge of motor rehabilitation among primary caregivers of stroke patients.Subjects and methods: A one-group pretest-posttest intervention study (without control) was conducted in 2025. A total of 103 primary caregivers of stroke inpatients undergoing rehabilitation were recruited. Caregiver knowledge was assessed before and after the intervention using a 20-item questionnaire covering four content domains.Results: The caregivers’ mean knowledge score increased from 9.1 ± 3.8 at baseline to 17.3 ± 2.0 post-intervention (p < 0.001). Knowledge scores across all four content domains improved significantly. Factors associated with greater knowledge gains included caregiver gender, educational level, source of information, and age. After the intervention, 88.3% of caregivers achieved a satisfactory knowledge level.Conclusion: The healthcare provider-led educational intervention significantly improved the motor rehabilitation knowledge of primary caregivers. This improvement is expected to enhance the effectiveness of post-stroke home care by addressing caregivers’ knowledge gaps.
Keywords: Stroke, primary caregivers, motor rehabilitation, educational intervention, knowledge improvement, post-discharge care.